The Effectiveness of Using E-Mail Applications in the Management of Incoming and Outgoing Letters at the Makassar Religious Education and Training Centre - Nasrullah, Muh.; Riska, Riska; Akib, Haedar (Pinisi Journal of Education and Management, 2022)
The Effectiveness of the Use of E-Mail Applications in the Management of Incoming and Outgoing Letters at the Makassar Religious Education and Training Centre Office. The information contained in a letter is very useful in future decision making as well as evidence and accountability of an organization. This research is a type of descriptive research, aiming to determine the effectiveness of the use of e-mail applications in managing incoming and outgoing letters at the Makassar Religious Education and Training Centre office. The informants in this study were the head of the Makassar BDK office, 2 archivists in charge, 2 administrative drafting staff. Data collection techniques used are observation, interviews and documentation. Data analysis techniques used are data collection, data condensation, data presentation, and conclusion/verification